Four new species of genus Acmella W.T. Blanford, 1869 (Gastropoda, Assimineidae) from Southern Thailand - Kunya Seedee; Pongrat Dumrongrojwattana; Supattra Poeaim (ZooKeys, 2025)
diversity in Thailand and shed light on biogeographical patterns found in this genus and the adaptations needed to survive under the conditions of cave systems.
Keywords: Mollusks and Parasites Studies; Aquatic Invertebrate Ecology and Behavior; Parasite Biology and Host Interactions